What are the effects of care bundles on the incidence of ventilator‐associated pneumonia in paediatric and neonatal intensive care units? A systematic review. Issue 4 (23rd July 2019) - Niedzwiecka, Teresa; Patton, Declan; Walsh, Simone; Moore, Zena; O'Connor, Tom; Nugent, Linda
Abstract: Purpose: The purpose of this review was to ascertain the impact of ventilator bundles on the incidence of ventilator‐associated pneumonia in mechanically ventilated neonates and children in intensive care units. Methods: A systematic review was conducted. Key computerised databases (CINAHL, Medline, Embase and Cochrane) as well as additional sources, with no publication date limitations, were extensively searched in January 2018. Inclusion criteria focused on ventilator bundles used in mechanically ventilated neonates and children aged from 0 to 18 years. After identification and inclusion, all studies were critically appraised for quality. Data were analysed and narratively synthesised. Results: Eight studies of observational and nonrandomised interventional methods design were included in the review. However, the validity of five of the eight studies which were reviewed was considered substandard. In addition, there were variations in the care bundles elements studied. Nevertheless, all these studies demonstrated that the incidences of VAP in mechanically ventilated neonates and children were found to be significantly reduced by the use of ventilator bundles. Practice Implications: This systematic review determines that ventilator bundles impact positively on the incidence of VAP in critically ill neonates and children in the neonatal intensive care unit and paediatric intensive care unit. However, the variations in the bundle elements and insufficient valid evidence necessitates further research in the area to validate the findings and to ensure standardisation of clinical practice. Prevention of VAP is aimed at avoiding the risk of aspiration in the lungs, colonisation of respiratory tract with pathogenic microorganisms and contamination of respiratory equipment. Moreover, the implementation of evidence‐based interventions grouped together is fundamental to improve patient outcomes. It is recommended that a further bona fide research is required to standardise the components of paediatric ventilator bundles.